Variabilidad hemodinámica entre Bupivacaína isobárica versus Bupivacaína hiperbárica aplicada en cesáreas de emergencia en el Hospital Regional de Loreto–2022 - Huamán Romero, Sergio Alfonso (2024)
OBJECTIVE: To evaluate the hemodynamic variability between hyperbaric bupivacaine and isobaric bupivacaine applied in emergency cesarean sections at the Regional Hospital of Loreto (HRL) 2022. MATERIALS AND METHODS: A quantitative, case-control study will be carried out, which will include the review of 100 case histories and 100 controls. A logistic regression analysis will be performed with 95% confidence applying SPSS v25 software. CONCLUSIONS: In the area of anesthesiology at the regional level where there is currently no evidence of differences in the hemodynamic impact of hyperbaric bupivacaine and isobaric bupivacaine in emergency cesarean sections, local information will be available.